1990
DOI: 10.1016/0749-596x(90)90069-c
|View full text |Cite
|
Sign up to set email alerts
|

Sentence memory: A theoretical analysis

Abstract: How sentences from a discourse are recognized or verified can be explained by combining theories of item recognition derived from list-learning experiments with hypotheses about the representation of text in memory within the framework of the construction-integration model of discourse comprehension. The implications of such a theory of sentence recognition are worked out for two experimental situations. In the first experiment, subjects read brief texts and were then tested for recognition with verbatim old s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
275
1
9

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(306 citation statements)
references
References 15 publications
19
275
1
9
Order By: Relevance
“…Also, studies examining memory over time have shown that memory for fine grained information deteriorates relatively rapidly, while memory for more coarse grained information endures (e.g., Christiaansen, 1980;Conway, Cohen, & Stanhope, 1991;Koriat, Levy-Sadot, Edry, & de Marcas, 2003;Stanhope, Cohen, & Conway, 1993). For example, memory for gist, or general meaning, endures longer than memory for surface form and verbatim information (e.g., Kintsch, Welsch, Schmalhofer, & Zimmy, 1990). There is also evidence that memory for categories is retained longer than memory for items (Dorfman & Mandler, 1994), and that there is a retention advantage of basic level information (Pansky & Koriat, 2004).…”
Section: Quantity and Accuracy Rates Across Retention Intervalsmentioning
confidence: 99%
“…Also, studies examining memory over time have shown that memory for fine grained information deteriorates relatively rapidly, while memory for more coarse grained information endures (e.g., Christiaansen, 1980;Conway, Cohen, & Stanhope, 1991;Koriat, Levy-Sadot, Edry, & de Marcas, 2003;Stanhope, Cohen, & Conway, 1993). For example, memory for gist, or general meaning, endures longer than memory for surface form and verbatim information (e.g., Kintsch, Welsch, Schmalhofer, & Zimmy, 1990). There is also evidence that memory for categories is retained longer than memory for items (Dorfman & Mandler, 1994), and that there is a retention advantage of basic level information (Pansky & Koriat, 2004).…”
Section: Quantity and Accuracy Rates Across Retention Intervalsmentioning
confidence: 99%
“…Because these tasks require students to go beyond the information they were given, inference and analogy tasks rely on the development of a situation model (Kintsch, Welsch, Schmalhofer, & Zimny, 1990). Thus, if the more transformed, integrated, and causal essays are related to the development of a model of the text, then students who write such essays should perform better on inference and analogy tasks, suggesting they have indeed gained a conceptual understanding of the subject matter.…”
mentioning
confidence: 99%
“…Therefore, source memory should be relatively constant across item types and presentation forms. More specifically, source memory is likely to be moderate or poor for all items because memory for surface information vanishes rather quickly when attention is directed toward semantic aspects of texts (see, e.g., Alba & Hasher, 1983;Kintsch & Ericsson, 1996;Kintsch, Welsch, Schmalhofer, & Zimny, 1990;Schmalhofer & Glavanov, 1986).…”
mentioning
confidence: 99%